Sales Planning and Strategy for Enterprise Resources Planning Application at PT. Kolega Moeda Berkarja - Masatia Darwin Mangaha Tatuhas; Stepani Sisca Wulandari (Management Research Studies Journal, 2023)
The advancement of information and communication technology has had a positive impact on the business sector in Indonesia, particularly for SMEs (Small and Medium-sized Enterprises). The SME industry in Indonesia holds significant potential in supporting the country's economy. The aim of this research is to analyze the sales strategy and planning of Enterprise Resources Planning (ERP) application at PT Kolega Moeda Berkarja. PT Kolega Moeda Berkarja provides Point of Sale (POS) application services that can be utilized by various types of businesses, especially micro, small, and medium-sized enterprises (SMEs) in Indonesia. The business types served by Kolega Moeda Berkarja include food & beverages and retail stores. The application's specifications encompass features like online cashier, employee management, accounting, and business analysis. Market research focuses on identifying factors causing problems to establish research issues. In an ever-evolving industry, Kolega Moeda Berkarja's application continues to keep up with the latest trends and updates its features and functionalities to remain relevant and competitive in the current business landscape. The development and enhancement of Kolega Moeda Berkarja's application features are driven by customer feedback, aiming to identify the needs and desires of SMEs stakeholders.